Coronavirus Disease 2019 (COVID‐19): Emerging detection technologies and auxiliary analysis. Issue 1 (10th December 2021) - Chen, Ying; Huang, Shengxiong; Zhou, Liuyan; Wang, Xin; Yang, Huan; Li, Wenqing
Abstract: The ongoing COVID‐19 pandemic constitutes a new challenge for public health. Prevention and control of infection have become urgent and serious issues. To meet the clinical demand for higher accuracy of COVID‐19 detection, the development of fast and efficient methods represents an important step. The most common methods of COVID‐19 diagnosis, relying on real‐time fluorescent quantitative PCR(RT‐qPCR), computed tomography, and new‐generation sequencing technologies, have a series of advantages, especially for early diagnosis and screening. In addition, joint efforts of researchers all over the world have led to the development of other rapid detection methods with high sensitivity, ease of use, cost‐effectiveness, or allowing multiplex analysis based on technologies such as dPCR, ELISA, fluorescence immunochromatography assay, and the microfluidic detection chip method. The main goal of this review was to provide a critical discussion on the development and application of these different analytical methods, which based on etiology, serology, and molecular biology, as well as to compare their respective advantages and disadvantages. In addition to these methods, hematology and biochemistry, as well as auxiliary analysis based on pathological anatomy, ultrasonography, and cytokine detection, will help understand COVID‐19 pathogenesis. Together, these technologies may promote and open new windows to unravel issues surrounding symptomatic and asymptomatic COVID‐19 infections and improve clinical strategies toward reducing mortality. Abstract : The main goal of this review was to provide a critical discussion on the development and application of these different analytical methods, which based on etiology, serology, molecular biology, as well as to compare their respective advantages and disadvantages. In addition to these methods, hematology and biochemistry, as well as auxiliary analysis based on pathological anatomy, ultrasonography, and cytokine detection, will help understand COVID‐19 pathogenesis.